Analisis Usaha Penggemukan Domba di Kelompok Ternak Sehati di Desa Sukorini, Kecamatan Manisrenggo, Kabupaten Klaten, Jawa Tengah - Kaloka, Aldita Barooch Safira; Junaidi, Aris (Jurnal Sain Veteriner, 2025)
Sheep is one of the sources of meat supply in Indonesia that is now increasingly in demand by the public, almost on par with the demand for goat meat. Therefore, efficient and profitable farming methods are needed. This study aims to analyze the sheep fattening business conducted by the Sehati Livestock Group in Sukorini Village, Manisrenggo District, Klaten Regency. The study lasted for three months using quality ewe lambs aged 8 months to 1 year with an initial weight of 15-25 kg. The methods applied included preconditioning to the fattening program in accordance with the Standard Operating Procedure (SOP), starting from arrival until the sheep were ready for sale. The main variables observed were body weight growth and income earned by the livestock group. The study was conducted on 44 sheep, with monthly body weight measurements and recording of all operational costs, including feed and medicine, to calculate the profit earned. The results showed that the average weight gain of sheep reached 6.42 ± 0.24 kg in three months. Thus, the Sehati Livestock Group earned a profit of Rp1,725,942 with an R/C ratio value of 1.03>1, indicating that this business has reached the optimal profit level. However, the fattening program carried out by the Sehati Livestock Group still requires evaluation in order to increase profitability in the future.